An exploratory study of schemes used by senior high school students to validate mathematic results - Larios Osorio, Dr. Víctor (Transformación, 2024)
Mathematics, as a body of scientific knowledge, includes not only a set of concepts and theories described in books and scientific journals but a procedural knowledge used for solving problems and proving the resulting solution. There is a tool for proving solutions, the so-called mathematical proof, which is worth to be included in the educational process. To complete the study herein described a random stratified sample was selected and given a test demanding to explain the answers given. However, high school students (15-18 years old) do not rely on the use of the known proof scheme. For that reason, a diagnostic study was carried out at the Autonomous University of Querétaro (UAQ) in order to identify the strategies the students are currently following and finding ways to teach such mathematical proof scheme. The findings are a description of individual students’ argumentative practices and the identification and grouping of the most frequently used proof scheme.
Keywords: mathematics instruction; mathematical concepts; abstract reasoning; deductive methods; learning